Nickel(II) Bisporphyrin‐Fused Pentacenes Exhibiting Abnormal High Stability. Issue 45 (1st September 2020) - Hu, Yi; Thomas, Michael B.; Webre, Whitney A.; Moss, Austen; Jinadasa, R. G. Waruna; Nesterov, Vladimir N.; D'Souza, Francis; Wang, Hong
Abstract: A series of largely π‐extended multichromophoric molecules including cross‐conjugated, half cross‐conjugated, conjugation‐interrupted and linearly conjugated systems were synthesized and characterized. These multichromophoric molecular systems revealed interesting structural‐property relationships. Bisporphyrin‐fused pentacenes Pen‐1 b and Pen‐2 a showed rich redox chemistry with 7 and 8 observable redox states, respectively. The linearly‐conjugated bisporphyrin‐fused pentacenes (Pen‐1 b and Pen‐2 a ) possess much narrower HOMO–LUMO gaps (1.65 and 1.42 eV redox, respectively) and higher HOMO energy levels than those of their pentacene analogues (2.23 and 2.01 eV redox, respectively), similar to those of much less stable hexacenes and heptacenes. An estimated half‐life of >945 h was obtained for bisporphyrin‐fused pentacene Pen‐2 a, which is much longer than that of its pentacene analogue (BPE‐P, half‐life, 33 h). Abstract : Cross and linearly conjugated largely π‐extended multichromophoric molecules have been prepared through incorporating both porphyrins and pentacenequinone/pentacene in one molecule. These multichromophoric molecular systems displayed interesting structure–property relationships. Linearly conjugated bisporphyrin‐pentacene molecules showed unusual stability.